Colchicine as a Strategic Therapeutic Alternative for Dengue-Associated Acute Pericarditis: Navigating the Hemorrhagic Risk - I Putu Agus Wijaya Putra; Tjokorda Prima Dewi Pemayun (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Dengue infection remains a pervasive arboviral disease in tropical regions, manifesting with a spectrum of clinical severities ranging from undifferentiated fever to life-threatening shock and severe hemorrhage. While cardiac involvement such as myocarditis is documented, acute pericarditis is an underrecognized complication that poses a unique therapeutic dilemma. The standard first-line anti-inflammatory treatment for pericarditis, specifically non-steroidal anti-inflammatory drugs (NSAIDs), is relatively contraindicated in dengue due to the inherent coagulopathy and thrombocytopenia associated with the disease. Case presentation: We report a case of a 53-year-old male presenting with high-grade fever, retro-orbital pain, and severe chest discomfort characteristic of pleuritis. Physical examination revealed a distinct pericardial friction rub and relative bradycardia (56 bpm). Laboratory analysis confirmed dengue infection with significant leukopenia (1.7 x 10³/µL), thrombocytopenia (49 x 10³/µL), and elevated liver transaminases. Electrocardiography (ECG) demonstrated diffuse ST-segment elevation, while echocardiography showed preserved ejection fraction (67.7%) without pericardial effusion. Diagnosed with dengue-associated acute pericarditis, the patient was ineligible for NSAIDs due to the high risk of gastrointestinal hemorrhage. He was successfully managed with low-dose Colchicine (0.5 mg daily) alongside standard supportive care. Rapid resolution of chest pain and normalization of ECG findings were observed within 48 hours without hemorrhagic complications. Conclusion: This case underscores the utility of Colchicine as a safe, effective, and strategic alternative to NSAIDs for managing acute pericarditis in thrombocytopenic dengue patients. Early recognition of the pericarditis triad in dengue is crucial to prevent mismanagement, and Colchicine should be considered a cornerstone of therapy in this specific clinical context.